Сучасний рівень імміграції в Україну - Коцан, Наталія Несторівна; Коцан, Вікторія Юріївна; Kotsan, N. N.; Kotsan, V. Y. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Вивчено кількість іммігрантів в Україні та встановлено їх частку в загальній кількості населення; досліджено національний склад іммігрантів. Вивчено проблемні сторони імміграції в Україні загалом, а зокрема процеси нелегальної імміграції. The number of immigrants in Ukraine and their share of the total number of population are studied; the ethnic composition of immigrants is analyzed. The problematic issues of immigration in Ukraine in general, and in particular the illegal immigration are researched.
The Current State of Ukraine Immigration
Keywords: імміграція; іммігрант; легальна імміграція; нелегальна імміграція; Україна; immigration; immigrant; legal immigration; illegal immigration; Ukraine